Handling child abuse victims through individual counselling at Seruni Semarang Integrated Empowerment Service Centre - Nisa, Hilmi Nasyithotun; Safrodin, Safrodin (Journal of Advanced Guidance and Counseling, 2025)
Purpose – This study aims to reveal the forms of child abuse and the individual counselling process carried out to treat child abuse victims at PPT Seruni. Method – This study is a field research with a qualitative approach and case studies. Primary data sources include informants from counsellors, assistants, victims of child abuse, foster mothers and shelter mothers. Result – The results of this study explain that there are various forms of child abuse among 14 child clients who are victims of violence. Five of them experienced sexual violence; four other clients were victims of psychological violence; two others experienced social violence in the form of neglect; and three others experienced physical violence. The impact of child abuse on these 14 children varied in severity, namely (1) moderate, (2) serious, and (3) fatal. To reduce these impacts, individual counselling was provided to them. This counselling was carried out in stages, including developing a relationship with the client, analysing the problem, explaining the problem, developing positive behaviour and making changes, as well as evaluation and follow-up to restore the client's condition. Implication – The implications of this study are to provide a theoretical contribution to the implementation of individual counselling in overcoming trauma in child victims of violence and also the various forms of violence against children. Originality/Value – This study on the handling of child abuse through individual counselling can contribute theoretically to the practice of individual counselling in handling child victims of violence at Handling child abuse victims through individual counselling at Seruni Semarang Integrated Empowerment Service Centre, as well as the various factors and forms of violence against children. *** Tujuan – Penelitian ini bertujuan untuk mengungkap bentuk-bentuk kekerasan terhadap anak dan proses konseling individu yang dilakukan untuk menangani korban kekerasan terhadap anak di PPT Seruni. Metode – Penelitian ini merupakan penelitian lapangan dengan pendekatan kualitatif dan studi kasus. Sumber data primer meliputi informan dari konselor, asisten, korban kekerasan terhadap anak, ibu asuh, dan ibu penampungan. Hasil – Hasil penelitian ini menjelaskan bahwa terdapat berbagai bentuk kekerasan terhadap anak di antara 14 klien anak yang menjadi korban kekerasan. Lima di antaranya mengalami kekerasan seksual; empat klien lainnya menjadi korban kekerasan psikologis; dua lainnya mengalami kekerasan sosial berupa penelantaran; dan tiga lainnya mengalami kekerasan fisik. Dampak kekerasan terhadap anak pada 14 anak ini bervariasi dalam tingkat keparahan, yaitu (1) sedang, (2) serius, dan (3) fatal. Untuk mengurangi dampak ini, konseling individu diberikan kepada mereka. Konseling ini dilakukan secara bertahap, termasuk membangun hubungan dengan klien, menganalisis masalah, menjelaskan masalah, mengembangkan perilaku positif dan melakukan perubahan, serta evaluasi dan tindak lanjut untuk memulihkan kondisi klien. Implikasi – Implikasi dari studi ini adalah memberikan kontribusi teoretis dalam implementasi konseling individu dalam mengatasi trauma pada korban kekerasan anak dan juga berbagai bentuk kekerasan terhadap anak. Orisinalitas/Nilai – Studi ini tentang penanganan kekerasan terhadap anak melalui konseling individu dapat memberikan kontribusi teoretis dalam praktik konseling individu dalam menangani korban kekerasan anak di PPT Seruni, serta berbagai faktor dan bentuk kekerasan terhadap anak.